2021
DOI: 10.1177/00332941211043456
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Relation Between Fear of Missing Out, Time Spent on the Phone, Sex, Alienation, and Nomophobia

Abstract: The prevalence of nomophobia is growing among adolescents. This study aimed to disentangle the relationship between nomophobia, the fear of missing out, time spent on the phone, sex, and social alienation. Participants, who were 595 students (313 females and 282 males) attending high school during the 2019–2020 academic year, filled out personal information forms and a series of scales involving nomophobia, the fear of missing out, and social alienation. Then, data were analyzed through a moderated mediation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…For example, research confirmed that stress furth promotes inappropriate mobile phone use among Chinese college students via FoMO [1 Wang et al [21] suggested that FoMO partially mediates the effects of stress on onl gaming disorders. Ergin and Ozer [20] showed a significant partial mediating role FoMO between social detachment and phobia. Some studies have confirmed the medi ing role of FoMO regarding the effect of social engagement on subjective well-being [1 Based on the above discussion, we suggested that COVID-19 lockdown stress mig impact college students' mental health through FoMO, and hypothesis 2 was propos COVID-19 lockdown stress was significantly positively correlated with FoMO; FoMO w significantly negatively correlated with mental health; and FoMO plays a mediating r between the COVID-19 lockdown stress and college students' mental health.…”
Section: Mediating Role Of Fomomentioning
confidence: 89%
See 3 more Smart Citations
“…For example, research confirmed that stress furth promotes inappropriate mobile phone use among Chinese college students via FoMO [1 Wang et al [21] suggested that FoMO partially mediates the effects of stress on onl gaming disorders. Ergin and Ozer [20] showed a significant partial mediating role FoMO between social detachment and phobia. Some studies have confirmed the medi ing role of FoMO regarding the effect of social engagement on subjective well-being [1 Based on the above discussion, we suggested that COVID-19 lockdown stress mig impact college students' mental health through FoMO, and hypothesis 2 was propos COVID-19 lockdown stress was significantly positively correlated with FoMO; FoMO w significantly negatively correlated with mental health; and FoMO plays a mediating r between the COVID-19 lockdown stress and college students' mental health.…”
Section: Mediating Role Of Fomomentioning
confidence: 89%
“…Wang et al [21] suggested that FoMO partially mediates the effects of stress on online gaming disorders. Ergin and Ozer [20] showed a significant partial mediating role of FoMO between social detachment and phobia. Some studies have confirmed the mediating role of FoMO regarding the effect of social engagement on subjective well-being [19].…”
Section: Mediating Role Of Fomomentioning
confidence: 91%
See 2 more Smart Citations
“…Specifically, in adolescents and young adults nomophobia is more common. 9,[21][22][23] In fact, the prevalence of nomophobia among university students is on the order of 100%. A recent metaanalysis confirmed that 25% of college students had mild nomophobia, over 50% had moderate nomophobia, and about 20% had severe nomophobia.…”
Section: Introductionmentioning
confidence: 99%